To the question of training of musicians-instrumentalists in higher education institutions of Ukraine - Аndriy Dushniy; Andrii Stashevskyi; Inna Stashevska; Vіtalіy Zaets; Oleksandr Benziuk (Universidade Estadual Paulista Júlio de Mesquita Filho, 2022)
The aim of the article is to theoretically substantiate the effectiveness and describe the practical application of the method of increasing the hermeneutic competence of instrumental students. The curriculum "Hermeneutics as a basis for understanding the musical text" emphasizes the formation of hermeneutic competence, which consists in the ability of the musician-instrumentalist to perform hermeneutic analysis of the musical text. This primarily involves: understanding the creative composition of the composer, the ability to "penetrate" into the work in order to convey pathos to the recipients; analyze in terms of "hermeneutic circle"; explaining the cultural and historical aspect of the work, in particular the author's biography and his aesthetic preferences. The proposed system of formation of hermeneutic competence within the training of a musician-instrumentalist in higher education allows to educate an interpreter who accurately reproduces the author's idea of the composer, while expressing his own performing skills.